Digitalna domoznanska zbirka - Resman, Simona (Knjižnica, 2005)
Local studies and local studies departments reflect the entire spectrum of knowledge within the local community. Transition to the new digital environment means just continuing the basic functions of local studies collections: acquisition, cataloguing and preservation of materials in different formats on different media. The background of each digital library is the technical architecture of system that enables interaction between the user and the library, saving digital material and building a platform for searching and indexing digital objects. Using advanced ICT requests from librarians, designers of digital local studies collections a reflection about traditional roles. A digital local studies collection with new technology enlarges local boarders, local contents become more and more interesting for a wider sphere of people. In collecting of local materials a collaboration with archives and museums, with academic community, with community groups and with individuals comes in forefront. Digital local studies collections with their contents support local diversity, lifelong learning and social inclusion. The crucial elements of a digital local studies collection are attractive local contents with fast and simple access from one place - a portal. In the digital age public libraries become managers of knowledge also by establishing digital local studies collections.
Keywords: splošne knjižnice; domoznansko gradivo; domoznanske zbirke; digitalizacija; digitization; computer science; računalništvo